CERDAS DIGITAL MARKETING DI ERA DIGITAL PADA SMK Al AMANAH, TANGERANG SELATAN - Ratnasari, Fina; Handayani, Puspita; Rahma, Ayumi (Fokus ABDIMAS, 2024)
This Community Service Program (PKM) aimed to provide knowledge and skills in accounting bookkeeping and digital marketing strategies through social media for students at SMK Al-Amanah. The program was conducted by the faculty team from the Bachelor's Degree in Accounting program, Faculty of Economics, Universitas Pamulang, using a method that involved lectures, mentoring, and hands-on practice. Participants were taught the basic concepts of digital marketing, the use of social media for business, and the importance of proper financial bookkeeping. The steps taken included presenting product marketing materials, providing guidance on the implementation of online marketing, and evaluating the training with practical exercises such as creating digital marketing content like Instagram Stories. The training was attended by 27 students, who showed high enthusiasm and actively participated in discussions and practical activities. The results of the activity indicated that participants’ understanding of digital marketing improved, and they were able to apply this knowledge in a business context. By using social media platforms such as Instagram and Facebook, participants were able to grasp strategies that could reach wider markets at more cost-effective rates. The training also emphasized the importance of creativity and digital security in online marketing. In the future, this PKM activity can be expanded to reach a broader audience, with more diverse topics, and conducted offline to further enhance the effectiveness of learning and its impact on the participants. Keywords: Community Service, digital marketing, accounting bookkeeping, social media, marketing strategy.